Implementasi Manajemen Sumber Daya Manusia Dalam Organisasi Pos Paud Terpadu Tulip Rungkut Tengah - Farchan Candra Utama; Alfiandi Imam Mawardi (STIKes Ibnu Sina Ajibarang, 2023)
Human Resource Management (HRM) plays a crucial role in organizational development, including in Early Childhood Education (ECE). The focus of this research is Tulip Integrated PAUD in Rungkut Tengah Village, Surabaya. Early childhood (0-6 years) enters the golden age period where their learning patterns are based on imitation. This research aims to improve the effectiveness of early childhood learning and socialization at Tulip Integrated PAUD through the implementation of HRM. The main problems involve children's diverse characters, lack of activities, and differences in parents' mindsets. The implementation method consists of four stages: (1) introduction to the members of Tulip Integrated PAUD, (2) introducing the concept of HR Management, (3) providing active and expressive learning to students, and (4) evaluation and monitoring.The results showed that the socialization of HR Management positively contributed to the management of human resources at Tulip Integrated PAUD. Emphasis on fun and expressive teaching patterns increases early childhood participation in learning and social activities. Continuous evaluation and monitoring are needed to ensure continuity and improvement. In conclusion, the implementation of HRM and engaging learning approaches can improve the effectiveness of PAUD organizations. It creates a conducive environment for optimal early childhood development, by involving teachers, committees, and parents as part of integrated human resource management.